Unseen Lives - Making Transgender Identities Visible: Dominant Social Perceptions of the Transgender Community in Urban Sri Lanka - Samaraweera, H. Unnathi S. (University of Colombo, 2015)
Transgender is a hidden and a 'tortured' sexual minority which is invisible within the larger hetero-normative value oriented Sri Lankan context due to the lack of support from the wider social, cultural and legal fields, 'f here is relatively little written by social science scholars regarding LGBT identity in Sri Lanka. Among what is available, only a few directly address the issue of transgender identity. Much of this literature also focuses on sex workers and not on ordinary persons living in society as transgender individuals. Within this context, I conducted a qualitative study using ten case studies of those living with a transgender identity including six transgender women and four transgender men in the Sri Lankan urban context.
Keywords: Transgender, Violence, Marginalization, Discrimination